The Effectiveness of Guided Inquiry Learning Model to Improve Students' Critical Thinking Skills on Acid-Base Materials - Siti Rohmah; Emmawaty Sofya; Tasviri Efkar; Bayu Saputra (Jurnal Pendidikan dan Pembelajaran Kimia, 2020)
This research was aimed to describe the effectiveness of guided inquiry learning model in improving students' critical thinking skills on acid-base material. The population in this study were students of class XI MIA SMA Negeri 3 Metro  of the 2019/2020 school year with a sample of class XI MIA 2 as the experimental class and XI MIA 3 as the cotrol class. This research method is a quasi-experimental with pretest postest control group design. The effectiveness of guided inquiry learning modelThis research was analyzed using the two mean difference test at n-Gain and the effect size test on students' critical thinking skills between experimental  class that applied guided inquiry learning model and control class. The results showed that  guided inquiry learning model had a "large" effect on improving students' critical  thinking skills with effect size about 0.94.The conclusion of this research is the guided inquiry learning model is effective for improving students' critical thinking skills.Keywords:acid-base, critical thinking, guided inquiry learning model. Penelitian ini bertujuan untuk mendeskripsikan efektivitas model pembelajaran inkuiri terbimbing untuk meningkatkan keterampilan berpikir kritis siswa pada materi asam basa. Populasi dalam penelitian ini adalah siswa kelas XI MIA SMA Negeri 3 Metro tahun ajaran 2019/2020 dengan sampel kelas XI MIA 2 sebagai kelas eksperimen dan XI MIA 3 sebagai kelas kontrol. Metode penelitian ini adalah kuasi eksperimen dengan pretest postest control grup design. Penelitian ini di analisis menggunakan uji perbedaan dua rata-rata pada n-Gain dan uji effect size terhadap keterampilan berpikir kritis siswa antara kelas eksperimen yang diterapkan model pembelajaran inkuiri terbimbing dan kelas kontrol. Hasil penelitian menunjukkan bahwa model pembelajaran inkuiri terbimbing  berpengaruh “besar” dalam meningkatan keterampilan berpikir kritis  siswa dengan effect size sebesar 0,94.Kesimpulan dari penelitian ini yaitu model pembelajaran inkuiri terbimbing efektif untuk  meningkatkan keterampilan berpikir kritis.Kata kunci:asam basa, kemampuan berpikir kritis, model pembelajaran inkuiri terbimbing